The study demands and resources scale: psychometric properties, longitudinal invariance, and criterion validity - van Zyl, Llewellyn E.; Shankland, Rebecca; Klibert, Jeff; Verger, Nicolas B.; Rothmann, Sebastiaan; Cho, Vincent; Feng, Katherine; See-To, Eric W. K.; Roll, Lara C.; Ghosh, Anindita; van der Meij, Leander; Arijs, Diane; et al. (Frontiers in Education, 2024)
The Study Demands and Resources Scale (SDRS) has shown promise as a valid and reliable measure for measuring students’ specific study demands and -resources. However, there is no evidence as to its psychometric properties outside of the original context in which it was developed. This study aimed to assess the psychometric properties of the SDRS in a cross-national student population through examining its longitudinal factorial validity, internal consistency, and temporal invariance as well as criterion validity through its association with study engagement and task performance over time. Results showed that a Bifactor Exploratory Structural Equation Model (ESEM) with one general factor (overall study characteristics) and five specific factors (workload, growth opportunities, lecturer support, peer support, information availability) fitted the data, showed strong measurement invariance over time, and was reliable at different time points. The study further established criterion validity for the overall study characteristics factor through its concurrent and predictive associations with study engagement and task performance. However, the specific factors’ concurrent and predictive capacity could only partially be established when controlling for the general study characteristics factor. These findings suggest that study characteristics should be measured as a dynamic interaction between study demands and resources, rather than a hierarchical model.